ANALISIS KEMANDIRIAN BELAJAR PESERTA DIDIK SMAN 96 JAKARTA - Dwi Rahayu, Endang; Asni (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
Self-learning is a form of learning that is driven by the ability, decision, and responsibility of the student in learning. If the student is able to complete his or her learning tasks consciously and without the help of others, then he or she can be considered to have studied independently. Self-reliance in learning is important because to measure how much learning can be achieved, it is done by taking the initiative and conducting the learning process at school. Therefore, the students are now responsible for the learning process and they try as hard as they can to ensure that the process of learning succeeds in order to what they want. This study uses a quantitative descriptive approach, with a simple random sampling technique. The study has a sample of 154 people. The questionnaires are used to collect data and use percentage formulas to analyze data. Based on the analysis of data from the independent learning research, students are in the middle category with a percentages of 72%, in the high category with 21%, and in the low category with 6%. This suggests that students need to improve their learning independence with the support and assistance of educators at school.